The association between dietary intake, lipid and glucose profile, and cognitive function among older adults with possible sarcopenia and sarcopenia in kelantan: a cross-sectional study - Abdullah, Nurul Syafiqa (Universiti Sains Malaysia, 2024)
Sarcopenia is the age-related progressive loss of muscle mass and strength. Dietary intake, glucose and lipid profile are extremely related to the cognitive function among older adults with possible sarcopenia and sarcopenia. The aim of this study was to explore the association between dietary intake, lipid and glucose profile and cognitive function among older adults with possible sarcopenia and sarcopenia in Kelantan. A cross-sectional study was conducted among 92 older adults using convenience sampling technique in several districts in Kelantan including Tumpat, Pasir Mas, and Kota Bharu aged 60 years old and above. Out of 92 subjects (51 males and 41 females), it was discovered that 9 females (22.0%) and 3 males (5.9%) were having dementia while 13 females (31.7%) and 13 males (25.5%) had mild cognitive impairment (MCI). Socio-demographic background, medical history, and dietary intake pattern were included during the interview session. Diet History Questionnaire (DHQ) was used to assess the dietary intake, Montreal Cognitive Assessment (MoCA) was used to detect cognitive dysfunction and early signs of dementia while Hand Grip Strength (HGS), Skeletal Muscle Index (SMI), and Short Physical Performance Battery (SPPB) were used to see the muscle strength and physical performance. However, there are no significant associations between dietary intake, glucose profile and lipid profile except high density lipoprotein (HDL). The findings of this study demonstrated that cognitive status alone was significant among the participants (p=0.015). The blood glucose results show that the median is 5.60 mmol for males, while it is 5.30 mmol for females which (p=0.546). For the lipid profile, only HDL is significant with (p=0.001), where the median is 1.23 mmol for males and 1.50 mmol for females. Other lipid profile results include as triglycerides, low-density lipoproteins (LDL), and total cholesterol are not significant. In addition, all macronutrients and micronutrients are not significant at all for dietary intakes results. Nevertheless, it is recommended that further studies be conducted to provide a clearer understanding of the relationship between dietary intake, lipid, and glucose profiles with cognitive function, as these factors are directly linked to cognitive function status.